PENGARUH TIME BUDGET PRESSURE, LOCUS OF CONTROL DAN PERILAKU DISFUNGSIONAL AUDIT TERHADAP KINERJA AUDITOR - I Nyoman Gede Arya Diatmika; Putu Ayu Pande Riani Savitri (Universitas Pendidikan Nasional, 2020)
The Influence of Time Budget Pressure, Locus Of Control and Dysfunctional Audit Behavior on Auditor Performance (Case Study in Bali Public Accounting Firm). This study aims to determine the effect of Time Budget Pressure, Locus of Control, and Dysfunctional Audit Behavior on Auditor Performance in the Bali Region Public Accounting Firm. The population in this study were auditors at the Bali Regional Public Accounting Firm with a sample of 63 auditors. Using purposive sampling technique in sampling. The data collection technique used in this study was a questionnaire with a Likert scale. The type of data in this research is quantitative data. The analysis method used is data analysis validity test, reliability test, classical assumption test, multiple regression analysis. Partial Significant Test (T Test) and Coefficient of Determination, the results of this study indicate that the Time Budget Pressure and Dysfunctional Audit Behavior have a partial negative effect on auditor performance while Locus of Control has a positive and significant effect on auditor performance Keywords: Time Budget Pressure, Locus Of Control, Dysfunctional Audit Behavior and Auditor Performance.